Factors that Influence the Performance of Lecturers in Lampung Indonesia - Erie Hermawan Atmawidjaja; Soewarto Hardhienata; Rita Retnowati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Lecturers are required to have good quality in the competencies that must be mastered. Lecturers should be able to master their fields well so that students can absorb all the knowledge given. This research uses quantitative methods. The data was processed using SPSS 21. The respondents were 214 lecturers. The data is processed by an assumption test. The assumption test used is the coloniality and reliability test. The data is followed by regression analysis and the calculation of multiple correlation coefficients. The results show that there is an influence of work motivation on lecturer performance; there is an effect of transformational leadership on lecturer performance, there is an influence of organizational culture on lecturer performance. There is a simultaneous influence of work motivation, leadership transformation, and organizational culture on lecturer performance.